The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1999
DOI: 10.1046/j.1525-1497.1999.05398.x
|View full text |Cite
|
Sign up to set email alerts
|

Variation by specialty in the treatment of urinary tract infection in women

Abstract: To determine practicing physicians' strategies for diagnosing and managing uncomplicated urinary tract infection, we surveyed physicians in general internal medicine, family practice, obstetrics and gynecology, and emergency medicine in four states. Responses differed significantly by respondents' specialty. For example, nitrofurantoin was the antibiotic of first choice for 46% of obstetricians, while over 80% in the other specialties chose trimethoprim-sulfamethoxazole. Most surveyed said they do not usually … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2001
2001
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(18 citation statements)
references
References 9 publications
(10 reference statements)
0
18
0
Order By: Relevance
“…16 An antibiotic agent is prescribed in 67% of visits, and a urinalysis is ordered in 81%, 16 with wide variations in physician management. 17,18 As many as 40% of antibiotics prescribed may be unnecessary because the subsequent urine culture result is negative. 4 The cystitis decision aid is a simple clinical approach that could reduce practice variation as well as unnecessary antibiotic prescriptions and urine culture testing.…”
Section: Commentmentioning
confidence: 99%
See 1 more Smart Citation
“…16 An antibiotic agent is prescribed in 67% of visits, and a urinalysis is ordered in 81%, 16 with wide variations in physician management. 17,18 As many as 40% of antibiotics prescribed may be unnecessary because the subsequent urine culture result is negative. 4 The cystitis decision aid is a simple clinical approach that could reduce practice variation as well as unnecessary antibiotic prescriptions and urine culture testing.…”
Section: Commentmentioning
confidence: 99%
“…5 This latter approach was associated with a high rate of unnecessary antibiotic use in the present study. In the context of increasing uropathogen antibiotic resistance 19 and lack of clinical agreement about how to manage acute cystitis, 17,18 practical and validated strategies that can help physicians use antibiotics judiciously could be clinically useful.…”
Section: Commentmentioning
confidence: 99%
“…In the recent years, several studies have shown specific risk factors for recurrent AUC [7,8] and large studies revealed its microbial etiology. Clinical tests for diagnosing AUC vary widely, depending on comorbidities and different treatment strategies [9,10,11]. …”
Section: Introductionmentioning
confidence: 99%
“…Often this test is used in conjunction with or in place of a urine culture in the diagnosis of a UTI. However, a recent study found many practicing clinicians use different standards to determine the presence or absence of a UTI, most not updated on current literature 3 . To further complicate matters, the level of automation in urinalysis is increasing and accepted cut-off values differ for these more sensitive methods.…”
mentioning
confidence: 99%